2014
DOI: 10.1016/j.chemosphere.2014.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of antimony(V) adsorption–desorption and transport in soils

Abstract: h i g h l i g h t sSb(V) sorption on soils were timedependent and irreversible. Retention mechanisms were different for acidic red soil and calcareous soil. Sb(V) transport in soils dominated by non-equilibrium reactions. Kinetic reversible-irreversible MRM formulation well described experiment results. Antimonate [Sb(V)] adsorption-desorption and transport in an acidic red soil (Yingtan) and a calcareous soil (Huanjiang) was investigated using kinetic batch and miscible displacement experiments. Different for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
1
14
2
Order By: Relevance
“…Extensive retention and low mobility of Sb(III) was found in the two soils before 100 pore volumes of Yingtan soil and 150 pore volumes of Huanjiang soil. This result was different with the result of Sb(V) study by Zhang et al [28] in the same two soils. In their study Sb(V) can easily breakthrough the soil column of Huanjiang soil, while for Yingtan soil Sb(V) was extensive retention.…”
Section: Breakthrough Curvescontrasting
confidence: 99%
See 4 more Smart Citations
“…Extensive retention and low mobility of Sb(III) was found in the two soils before 100 pore volumes of Yingtan soil and 150 pore volumes of Huanjiang soil. This result was different with the result of Sb(V) study by Zhang et al [28] in the same two soils. In their study Sb(V) can easily breakthrough the soil column of Huanjiang soil, while for Yingtan soil Sb(V) was extensive retention.…”
Section: Breakthrough Curvescontrasting
confidence: 99%
“…The adsorption isotherms of Sb tot in Fig. 2 was different from Sb(V) adsorption results from our previous study [28], which showed that the adsorption of Sb(V) in Yingtan soil was much higher than in Huanjiang soil. This is because that Sb(V) adsorption was dramatically influenced by solution pH while Sb(III) can be adsorbed in a wide range of pH [35].…”
Section: Sorption Isothermscontrasting
confidence: 67%
See 3 more Smart Citations